2020
DOI: 10.1371/journal.pone.0232365
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the BRAF V595E mutation in plasma cell-free DNA from dogs with urothelial carcinoma

Abstract: Circulating tumor DNA (ctDNA), which carries tumor-specific mutations, is an emerging candidate biomarker for malignancies and for monitoring disease status in various human tumors. Recently, BRAF V595E mutation has been reported in 80% of dogs with urothelial carcinoma. This study investigates the BRAF V595E allele concentration in circulating cellfree DNA (cfDNA) and assesses the clinical significance of BRAF-mutated ctDNA levels in canines with urothelial carcinoma. A total of 15 dogs with urothelial carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Second, cfDNA is a very sensitive diagnostic biomarker for inflammation; therefore, it is difficult to completely rule out the possibility of elevated cfDNA levels in non-specific inflammation in vivo . Real-time PCR techniques with high specificity can be used to determine the underlying inflammatory mechanisms ( 24 27 ). Third, the observation period was short (up to 60 weeks), and each individual case had a different time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Second, cfDNA is a very sensitive diagnostic biomarker for inflammation; therefore, it is difficult to completely rule out the possibility of elevated cfDNA levels in non-specific inflammation in vivo . Real-time PCR techniques with high specificity can be used to determine the underlying inflammatory mechanisms ( 24 27 ). Third, the observation period was short (up to 60 weeks), and each individual case had a different time frame.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of canine mammary carcinoma, ctDNA detection was demonstrated using digital PCR assays specific to somatic genomic rearrangements in 4 dogs (Beck et al 2013). In another study, ctDNA detection was demonstrated in 8 of 11 dogs with urothelial carcinoma using a real-time PCR assay for a recurrent somatic mutation in BRAF (Tagawa et al 2020). Earlier, we demonstrated detection of ctDNA in 2 of 6 dogs with pulmonary adenocarcinoma using a digital PCR assay for a recurrent somatic mutation in ERBB2 (Lorch et al 2019).…”
Section: Introductionmentioning
confidence: 87%
“…However, published experience with ctDNA analysis in dogs is currently sparse. Nonetheless, limited and small-scale published studies have suggested total cell-free DNA concentrations are higher in dogs with malignant tumors compared to those with benign disease or healthy controls (Schaefer et al 2007;Beffagna et al 2017;Tagawa et al 2020). In a recent study of canine mammary carcinoma, ctDNA detection was demonstrated using digital PCR assays specific to somatic genomic rearrangements in 4 dogs (Beck et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One example already in diagnostic use is the previously mentioned BRAF mutation for the detection of UC. A recent advance of this approach has been the demonstration that mutated BRAF can be detected in blood samples from these patients (Tagawa et al 2020). A prognostic example is PARR in combination with quantitative PCR for monitoring residual disease burden in canine lymphoma patients.…”
Section: Identification Of Novel Biomarkers and Therapeutic Targets To Predict Ideal Therapy Choicesmentioning
confidence: 99%